The Indians, independence and the "colonial heritage": Some reflections - Méndez, Cecilia (1990)
It is commonplace in the Peruvian social sciences to appeal to the "colonial heritage" to explain the root of our social ills. No one with a minimum of lucidity and sensitivity to the environment that surrounds us could categorically reject such a statement. Almost two centuries ago Peru broke with Spain, but the wound of the conquest still festers. Well, in our country (and apart from the notable advances of the post-Velasquist era), what is cholo, what is Indian, what is Quechua, what is obscure and what is not, linguistically speaking, "Castilian", continues to be despised.